Pengaruh Motivasi dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada Kantor Cabang Pegadaian Kelapa Dua Depok - Iqbal Saputra; Taat Kuspriyono; Yunidyawati Azlina (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of motivation and physical work environment on employee performance at the Pegadaian Branch Office in Kelapa Dua, Depok. The method used is a quantitative approach with the distribution of questionnaires to 33 respondents as samples. This study uses a saturated sampling technique. The data analysis was conducted using IBM SPSS version 21 through validity tests, reliability tests, classic assumption tests (normality, multicollinearity, heteroscedasticity), multiple linear regression tests, T tests, F tests, and determination coefficients. The results show that both motivation and physical work environment partially have a positive and significant effect on employee performance. Motivation contributes 50.4%, while the physical work environment contributes 50.9%. Simultaneously, both motivation and physical work environment together have an influence on employee performance of 63.8%. Meanwhile, the rest is influenced by other factors that were not examined in this research. Based on the results of this study, it can be concluded that increasing motivation and improving the physical work environment can effectively enhance employee performance. These findings are expected to serve as a reference for management in making human resource policy decisions. Future researchers are encouraged to increase the number of respondents and introduce other variables to obtain more detailed analysis results.